Impact of Hydrophobicity on Wetting Characteristics of Composite Insulators - Jikai Bi; Yanpeng Hao; Lin Yang; Yao Zheng; Licheng Li (IEEE Access, 2020)
To perfect the wetting mechanism of hydrophobic insulators, it is urgent to explore the impact of hydrophobicity on wetting characteristics of the pollution layer of composite insulators. In this article, the wetting test of the hydrophobic pollution layer was carried out in artificial hot fog. The local surface conductivity of the pollution layer with different hydrophobicity were measured. The test results show that the local surface conductivities of different hydrophobic pollution layers are obviously different at the same wetting time. For researching the regularity of wetting process in greater detail, three characteristic quantities were proposed to represent the wetting characteristics. They are the duration of local surface conductivity close to zero (DLSCCZ), the saturated wetting time (SWT) and the maximum value of local surface conductivity (MVLSC). With the enhancement of hydrophobicity of the pollution layer, DLSCCZ and SWT increase, while MVLSC and the growth velocity of local surface conductivity both decrease.